Factor analysis of the Approaches and Study Skills Inventory for Students in a cross‐cultural occupational therapy undergraduate student sample. (31st July 2018) - Bonsaksen, Tore; Småstuen, Milada C.; Thørrisen, Mikkel M.; Fong, Kenneth; Lim, Hua Beng; Brown, Ted
Abstract : Background/aim: The Approaches and Study Skills Inventory for Students (ASSIST) has been used previously to assess the learning approaches among students in higher education, but reports of its use with occupational therapy students are rare. This study investigated the factor structure of the ASSIST in a cross‐cultural sample of undergraduate occupational therapy students, and examined whether the factor structure from specific participant groups from different cross‐cultural contexts was consistent. Methods: Occupational therapy students ( n = 712) from education programmes in Australia, Norway, Hong Kong and Singapore completed the ASSIST. To assess the factor structure of the instrument, a Principal Components Analysis (PCA) using a confirmatory approach, was completed. Cronbach's coefficient α and inter‐item correlations were used to assess the internal consistency of the ASSIST and its subscales. Results: For the whole sample, the PCA confirmed the three primary factors as previously established. Five subscales loaded on the first factor ( strategic approach). Four subscales loaded on the second factor ( surface approach), whereas the remaining four subscales loaded on the third factor ( deep approach). Repeating the analysis for each of the country‐specific samples produced slightly diverging factor structures for the samples from Australia and Hong Kong. Conclusion: Considering all the data, the ASSIST subscales that emerged from the PCA used with a confirmatory approach in this study revealed a good degree of concordance with the established original factor, scale and subscale structure. The slightly deviating results obtained for the Hong Kong student group indicate that the established factor structure may not be the best fit across all settings, cultural contexts and sample groups.